Autonomous lawnmower using peripheral interface microcontroller (PIC): article - Yahya, Nurhidayah (UiTM, 2007)
This project is about an autonomous lawnmower using a peripheral interface controller. This project is using PIC16f873 to program the task regarding to the movement of the lawnmower. The autonomous lawnmower is programmed to automatically moving, which it takes two seconds after switch on. The Autonomous lawnmower will mow a field of grass. A borderline will be a layout on the surface of the field to ensure the movement of the autonomous lawnmower. The field of grass is considering having no obstacle. All hardware and software has been tested as separate modules followed by integration.